The Connection Between Family Economic Education and Entreprenurial Interest in University Students - Fitri Maulidya; Riza Yonisa Kurniawan (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2025)
Objective: This research seeks to examine the relationship between family economic education and the entrepreneurial interest of prospective economics teacher students. Method: This study employs a quantitative regression method with a survey to obtain primary data processed in SPSS. The results of this study found a negative and significant connection in relation to family economic education and the entrepreneurial interest of prospective teacher students at Surabaya State University. Results: The results of this study found a negative and massive relationship between family economic education and the entrepreneurial interest of prospective teacher students at Surabaya State University. This occurs due to the internalisation process and the conservative views of parents regarding the teaching profession that students will pursue. The indication lies in the preparation of all economic aspects for career purposes, rather than focusing on entrepreneurship. Novelty: This study uses a population of prospective economics teachers, which is rarely studied, with a research model related to the latest data. This can broaden the understanding of the broader contextual entrepreneurial interest.